Mechanical Properties of New Composite Wood-Plastic Formworks with Aluminum Alloy Frame - Kairong Shi; Jiebin Xu; Zhengrong Jiang; Junfeng Lv; Yonghui Lu (Advances in Civil Engineering)
Formwork engineering plays a crucial role in cost, efficiency, quality, and schedule in civil engineering. Currently, wood-plastic formwork, which has favorable mechanical properties such as wood and excellent stability, formability, ease of demolding, and time-saving as plastic, is earning its increasing reputation in construction. This work focuses on mechanical properties of two types of new composite wood-plastic formworks with aluminum alloy frame used for construction, that is, single-span simply supported and three-span continuous formworks. Experimental investigation shows that the two types of wood-plastic formworks demonstrate favorable performance, and the deflections and stresses are within the allowable range, thereby satisfying the structural bearing requirements. Numerical analyses confirm that the results of the refined and general finite element models are consistent with the experimental results, but the former has a higher accuracy. When the requirement of accuracy is not too strict, the general model is preferred, given the modeling convenience and high efficiency. On the basis of experimental and numerical investigations, practical simplified formulas are proposed to facilitate rapid calculation and evaluation considering transverse deflection and inconsistency of two materials. Therefore, the results in this work can provide a theoretical basis for developing and applying the new formworks.